Roberto Burle Marx landscape project for FAU-UFRJ: didactic possibilities through graphic representation of the trees - Sá Antunes Costa, Lucia Maria; Queiroz Abreu Torres, Yuri; Barcellos Pinheiro Machado, Denise; Horácio Fernandes, Maria Vitoria; de Carvalho de Oliveira, Nathalia (InfoDesign, 2022)
The Federal University of Rio de Janeiro campus has the privilege of having two projects from the most important Brazilian landscape designer, Roberto Burle Marx. This paper is part of a broader research aiming at the preservation and restoration of Burle Marx's landscape project for the Faculty of Architecture and Urbanism, acknowledging its relevance as a heritage which represents part of his scholarly legacy for the city of Rio de Janeiro. For this paper, the research explores the didactic potential of the trees and palms listed for the original landscape project, recognizing their value as a laboratory for architecture students. It looks at the graphic representation of the original landscape project, in which concepts and techniques of visual rhetoric were applied to help in the design of a graphic repertoire for the presentation of Burle Marx’s work. The study brings forward a set of information in a new way, concerning the trees and palms listed in the original project. This new graphic representation enables the framing of an exploratory environment, whose visualization of botanical information becomes a tool from which students can analyze, interpret and produce new meanings.